2016
DOI: 10.1590/abd1806-4841.20164250
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between alopecia areata and HLA class I and II in a southeastern Brazilian population

Abstract: BackgroundAlopecia areata (AA) is a common disorder of unknown etiology that affects approximately 0.7% to 3.8% of patients among the general population. Currently, genetic and autoimmune factors are emphasized as etiopathogenic. Studies linking Human Leukocyte Antigens (HLA) to AA have suggested that immunogenetic factors may play a role in the disease's onset/development.ObjectivesTo investigate an association between AA and HLA class I/II in white Brazilians. Methods: Patients and control groups comprised 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…18 In a Brazilian population, there was a lack of association between AA and HLA class I and II alleles. 19 These different results indicate that the role of HLA class I in the immunopathogenesis of AA could be modulated by environmental factors, and based on the results of our study, possibly by MICA STR alleles that could be linked to several HLA-B alleles. Further study on this is warranted.…”
Section: Genotypementioning
confidence: 45%
“…18 In a Brazilian population, there was a lack of association between AA and HLA class I and II alleles. 19 These different results indicate that the role of HLA class I in the immunopathogenesis of AA could be modulated by environmental factors, and based on the results of our study, possibly by MICA STR alleles that could be linked to several HLA-B alleles. Further study on this is warranted.…”
Section: Genotypementioning
confidence: 45%
“…Two allele families ( HLA-DRB1∗04 and HLA-DRB1∗16 ) conferred a significantly increased risk. For HLA-DRB1∗04 polymorphisms, the analysis of the pooled data of 8 case-control studies [ 9 16 , 20 ] revealed a significant increase in frequency (31.6% compared with 22.2% in controls), with an evidence of heterogeneity ( I 2 = 43.0%, P = .081). A random-effects model was used for calculating OR.…”
Section: Resultsmentioning
confidence: 99%
“…[ 12 – 14 ] However, the results were inconsistent with the findings of other studies. [ 15 – 20 ] Moreover, one study suggested a lower occurrence of HLA-DRB1∗15 polymorphisms in AA, [ 21 ] whereas others found no association. [ 13 , 15 , 16 , 18 20 ]…”
Section: Introductionmentioning
confidence: 99%
“…In a Brazilian population study, individuals with no familial history of alopecia areata but suffering from different degrees of this pathology were analyzed. They showed a higher frequency of the C*04 allele, but no other significant differences were found between the control groups (Barbosa et al, 2016). However, more recent studies that analyzed the top class I histocompatibility genes propose that HLA-A and B alleles represent a more significant risk factor than HLA-C alleles.…”
Section: Autoimmune Diseasesmentioning
confidence: 92%